2022
DOI: 10.3390/molecules27072321
|View full text |Cite
|
Sign up to set email alerts
|

Aprotic Ionic Liquids: A Framework for Predicting Vaporization Thermodynamics

Abstract: Ionic liquids (ILs) are recognized as an environmentally friendly alternative to replacing volatile molecular solvents. Knowledge of vaporization thermodynamics is crucial for practical applications. The vaporization thermodynamics of five ionic liquids containing a pyridinium cation and the [NTf2] anion were studied using a quartz crystal microbalance. Vapor pressure-temperature dependences were used to derive the enthalpies of vaporization of these ionic liquids. Vaporization enthalpies of the pyridinium-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…For the presently investigated ionic liquids, it varies from 136 ± 18 kJ/mol for m-C 6 H 4 (CH 2 ImMe)][NTf 2 ] 2 to 147 ± 12 and 147 ± 13 kJ/mol for [DABCO10][NTf 2 ] and [p-C 6 H 4 (CH 2 ImBu)][NTf 2 ] 2 , respectively, and finally to 180 ± 17 kJ/mol for [C 6 Py][NTf 2 ]. These values are consistent with those previously reported for the other ionic liquids [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For the presently investigated ionic liquids, it varies from 136 ± 18 kJ/mol for m-C 6 H 4 (CH 2 ImMe)][NTf 2 ] 2 to 147 ± 12 and 147 ± 13 kJ/mol for [DABCO10][NTf 2 ] and [p-C 6 H 4 (CH 2 ImBu)][NTf 2 ] 2 , respectively, and finally to 180 ± 17 kJ/mol for [C 6 Py][NTf 2 ]. These values are consistent with those previously reported for the other ionic liquids [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 93%
“…Bulow et al reported a comparison of the vapor pressure of ILs containing the same 1-ethyl-3-methyl-imidazolium cation and a series of anions, such as PF 6 , B(CN) 4 , (C 2 H 5 O) 2 PO 2 , NTf 2 , SCN, CF 3 CO 2 , CF 3 SO 3 , BF 4 , C(CN) 3 , (C 2 F 5 ) 3 PF 3 , 4-CH 3 -Ph-SO 3 [ 32 ]. Finally, in the last couple of years some models were also proposed to derive the vapor pressure and vaporization enthalpy values from the knowledge of the structure of ILs [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contributions for ΔlnormalgHmnormalo (CH 3 )=6.33 kJ mol −1 and ΔlnormalgHmnormalo (COOH)=44.0 kJ mol −1 are well‐established for the molecular liquids [69,70] . The principle transferability of the ΔlnormalgHmnormalo (R) contributions from molecular liquids to ionic liquids was explored and validated in our recent work [65,66] . Thus, the numerical value for the vaporization enthalpy of [HOOC‐CH 2 ‐py][NTf 2 ] was calculated as follows: ΔlnormalgHmnormalo (298.15 K)=(131.7−6.33+44.0) kJ mol −1 =169.4 kJ mol −1 (Figure 9).…”
Section: Resultsmentioning
confidence: 96%
“…The experimental determination of enthalpy of vaporization is a challenging task, so the experimental values must be validated with every theoretical method. A general approach to estimating enthalpies of vaporization based on a so‐called “centerpiece” molecule is under development in our recent work [65,66] . This approach is related to the conventional group additivity (GA), where the property of a molecule of interest is collected from a set of possibly small groups with well‐defined contributions [67] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation